Nursing Implementation of Plasticine Play Therapy In Children With Typhoid Fever With Anxiety Due To Hospitalization - Putri Mayana, Namira Gustiany; Rehana; Yunike (Yayasan Rumah Ilmu Professor, 2022)
Children with typhoid fever require the child to undergo hospital treatment. This condition is a threatening situation and can cause feelings of anxiety if the child is unable to adapt. One way to reduce the impact of hospitalization is plasticine play therapy. Method: The type of research used in this research is descriptive in the form of a case study to explore the implementation of nursing in children with typhoid fever with anxiety due to hospitalization. The case study subjects were two pediatric patients aged 3-6 years with the same nursing problems, namely typhoid fever patients with anxiety and were willing to become respondents by signing informed consent represented by the patient's family. This research was carried out in March 2023. Results: The results of this research show that reducing anxiety through plasticine play therapy is effective in reducing the anxiety experienced by pediatric patients during hospitalization. Conclusion: Actions that can be taken in children with typhoid fever with anxiety due to hospitalization can be plasticine play therapy.